1991
DOI: 10.1111/j.1749-6632.1991.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HP 029 (Velnacrine Maleate) in Alzheimer's Diseasea

Abstract: HP 029 (1,2,3,4-tetrahydro-9-aminoacridin-1-ol-maleate) is a cholinesterase inhibitor and one of a series of compounds synthesized at Hoechst-Roussel Pharmaceuticals Inc. (HRPI) as a potential therapeutic agent for senile dementia of the Alzheimer type (SDAT). An ongoing clinical development program for HP 029 (velnacrine maleate) reflects a rational, traditional progression from therapeutic concept through clinical evaluation. Prior to the initiation of outpatient studies, sufficient data had been obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…(1993) suggests that a correlation may exist with ALT elevations and tacrine or tacrine to metabolite (l-hydroxytacrine) plasma ratios. These findings are not definitive as 1-hydroxytacrine (velnacrine) administration is also known to produce ALT elevations (SCHNEIDER 1993;MURPHY et al 1991;CUTLER et a1. 1990a).…”
Section: B Clinical Experiencementioning
confidence: 88%
“…(1993) suggests that a correlation may exist with ALT elevations and tacrine or tacrine to metabolite (l-hydroxytacrine) plasma ratios. These findings are not definitive as 1-hydroxytacrine (velnacrine) administration is also known to produce ALT elevations (SCHNEIDER 1993;MURPHY et al 1991;CUTLER et a1. 1990a).…”
Section: B Clinical Experiencementioning
confidence: 88%
“…Velnacrine is, like THA, a centrally acting cholinesterase. It has been shown to have some effect in the treatment of Alzheimer's disease (24). In 1997, Eccles et al (25) showed that velnacrine inhibits the hepatic oxidative enzymes responsible for the metabolism of AP to OHA and NORA but not to HMA.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of AChE inhibitors, in general, is that cognitive response rates range from 30% to 60% among patients who can tolerate effective doses [30,[34][35][36].…”
Section: Principal Cholinesterase Inhibitorsmentioning
confidence: 99%